STRATEGI PEMBERITAAN DETIK.COM DALAM PENYEBARAN BERITA VIRAL DI WEBSITE WWW.DETIK.COM - Firda Susilawati; Djudjur Luciana Radjagukguk (Jurnal Ilmu dan Budaya, 2020)
Detik.com is an online news portal that prioritizes speed with accurate, credible, balanced and trusted news content. In this study, discussing the detik.com reporting strategy in spreading viral news on the website www.detik.com. The purpose of this research is to find out how the news strategy carried out by detik.com in spreading viral news on the website www.detik.com. This study uses qualitative methods and descriptive research types. Primary data were obtained from in-depth interviews with one Key informant and one informant, while secondary data was obtained through documentation and literature study. The key informant in this study was the Managing Editor, and the informant in this study was the journalist DetikNews.The theory that is relevant to this research is the POAC theory from George R Terry. And the concept of this research is news strategy, news dissemination, and website. The results of this study indicate that the detik.com reporting strategy in spreading viral news on the www.detik.com website is: holding meetings, reporting to the field, conducting a selection strategy for many developing issues, by verifying data and writing strategies by journalists covering in the field, write based on available facts.